Internet of Things Applied in Grain Reception Base - Mesaros, Diana; Duda, M; Moldovan, Cristina; Muntean, S (The scientific bulletin of Electrical Engineering Faculty, 2022)
The goal of this paper is to present the benefits of digitalization and Internet of Things applied in various fields of industry, including in cereal reception bases. Using Waterfall Methodology, this article widely describes the project plan of a web-based application which has the role of monitorization the grain storage sheds from perspective of temperature, humidity, pressure, and motion. Using microprocessor-based systems and distinct types of sensors such as temperature, humidity, pressure and motion, the information collected from the grain storage hall is displayed on a web-based application so that operators of the base easily can monitor these parameters.